Electrical wiring, residential - Mullin, Ray C. (Delmar Thomson Learning, 2002)
Electrical Wiring - Residential is a trusted resource for information on all aspects of house wiring, having been adopted as an essential component of numerous national training programs. One of the best selling books on residential wiring on the market for more than a decade, Electrical Wiring - Residential features hundreds of examples, calculations, plus full-color wiring diagrams, illustrations, and photos while conforming to the 2002 National Electrical Code (NEC). The book explains the Code's new metric numbering system while utilizing both metric and the prevalent English system. The book begins by introducing readers to the basics of wire sizing, load calculations, and wiring diagrams. It then proceeds to address relevant NEC rules and requirements, room by room, through an entire home. Discussion of the unique considerations of wiring a home for the handicapped, as well as an introduction to today's state-of-the-art home automation wiring, is also featured. A useful list of major electrical appliance manufacturers' web sites is provided in an appendix. When used together with the NEC, Electrical Wiring - Residential offers its readers an unparalleled, hands-on learning experience.